Penyelesaian Sengketa Dengan Mediasi Melalui Badan Pertanahan Nasional Antara PT. Meridan Sejati Surya Plantation Dengan Kelompok Tani Tunas Jaya di Kabupaten Siak Provinsi Riau. - Nanda Yusri Pratama (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Mediation is a form of dispute relation that bring the two sides that there is disagreement between the two parties in order to find a solution or a way out of the problem they face. This mediaton where both parties may issue his opinion of each of the existing problems and their expected path of peace between the two sides.Problems that occur between PT.Meridan with farmer groups shoots Jaya is done through legal channels is court, where PT.Meridan not willing to serve the demands of the farmers victoriuos through mediaton but by taking legal action in court.This type of research is descriptive sociological research conducted in PT.Meridan and farmer groups shoots victorious on land parcels HGU using pimary and secondary data. Of research and discussion lead to the conclusion that PT. Meridan stated that the land they have been obtained by lawful and has made payment of compensation to the land of people who are in a location HGU issued authorized officer.Keywords : dispute realtion-mediaton